Effect of thermoplastic resin transfer molding process and flame surface treatment on mechanical properties of carbon fiber reinforced polyamide 6 composite - Lee, Jungwoo; Lim, Jun Woo; Kim, Minkook (WILEY, 2020)
The thermoplastic resin transfer molding (T-RTM) process for carbon fiber reinforced thermoplastic polymer composites (CFRTP) were experimentally investigated and optimized using high-pressure resin transfer molding system for mass production. The CFRTP was manufactured by Anionic ring opening polymerization of the T-RTM process and the curing process was analyzed by in situ cure monitoring using dielectrometry. Mechanical properties, productivity, and crystal structures of the PA 6 matrix and CFRTP were evaluated by differential scanning calorimetry, X-ray diffraction analysis, tensile, and interlaminar shear strength tests. The crystallinity, impregnation quality and process speed were determined by the curing temperature. In addition, a time- and cost-effective flame surface treatment was developed to remove moisture from the carbon fiber and increase the interfacial bonding strength of the CFRTP. As a result, optimal T-RTM processing conditions were suggested for realizing maximum productivity and mechanical properties for the CFRTP.
Keywords: ANIONIC POLYAMIDE-6; POLYMERIZATION; CRYSTALLIZATION; CRYSTALLINITY; HUMIDITY; LACTAMS; TENSILE; WATER